2020
DOI: 10.1002/er.6240
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of different operating strategies of thermal energy storage with radiant cooling system

Abstract: Thermal energy storage systems in building cooling applications have been explored extensively as a peak load-shifting technology. Thermal energy storage performance has been recognized and studied from an energy cost-savings point of view because of peak-valley price differences, but not many studies have been conducted from an energy savings viewpoint. This study experimentally investigates the performance of the energy storage-retrofitted to a ceilingtype radiant cooling system. To study the performance, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 46 publications
(88 reference statements)
0
1
0
Order By: Relevance
“…Singh et al invented a phase-change ceiling radiant cooling system and applied the system based on the TOU price control strategy. The research results showed that the operating cost was reduced by at least 17.5% and up to 22.4% [20]. To take advantage of low-cost electricity for heating at night (11 p.m. to 8 a.m.), Lin et al developed an underground heating system with a shape-stable PCM plate.…”
Section: Introductionmentioning
confidence: 99%
“…Singh et al invented a phase-change ceiling radiant cooling system and applied the system based on the TOU price control strategy. The research results showed that the operating cost was reduced by at least 17.5% and up to 22.4% [20]. To take advantage of low-cost electricity for heating at night (11 p.m. to 8 a.m.), Lin et al developed an underground heating system with a shape-stable PCM plate.…”
Section: Introductionmentioning
confidence: 99%